Management of Extracurricular Activities at SMP Negeri 1 Wih Pesam Bener Meriah Regency - Moza Arita; Iis Marsitah; Najmuddin Najmuddin (Edumaspul: Jurnal Pendidikan, 2023)
The aim of this research is to describe the management of extracurricular activities at SMP Negeri 1 Wih Pesam, Bener Meriah Regency. This research uses a qualitative descriptive paradigm approach. Qualitative research is a research procedure that produces descriptive data in the form of written or spoken words from people who can be observed. In this research, the researcher tried to reveal and tell various forms of conditions, events and realities in the management of extracurricular activities at SMP Negeri 1 Wih Pesam, Bener Meriah Regency. The results of the research show that the planning for extracurricular activities that has been mutually agreed upon is very good because the school has involved all elements of the school, especially the head of student affairs, extracurricular supervisors, committees and parents by holding meetings to discuss the objectives of implementing extracurricular activities, scheduling extracurricular activities as well as the division of tasks and tasks. responsibilities of extracurricular supervisor teachers.